IT implementation in the educational process of future engineers by means of project activities and competences assessment; Global Engineering Education Conference (EDUCON), 2013 IEEE, 13-15 March 2013, Berlin, Germany - Zamyatina O. M. Oksana Mikhailovna (2013, 2013)
Title screen